(untitled) (Bangladesh Journal of Child Health, 2013)
Magneting resonance imaging in subacute sclerosing panencephalitis (SSPE) usually demonstrates changes in periventicular and subcortical white matter. Basal ganglia, Cerebellum, Spinal cord are less commonly involved. In this article, we report two cases of SSPE associated with basal ganglia involvement. The 1st case a 11 years old boy had the severe symptoms of SSPE with bilateral basal ganglia involvement. The 2nd case a 8 years old girl had right sided hemiplegia. DOI: http://dx.doi.org/10.3329/bjch.v36i3.14289 BANGLADESH J CHILD HEALTH 2012; VOL 36 (3) : 153-155